Equilibrium price dynamics in an overlapping-generations exchange economy - Brito, Paulo (2010)
We present a continuous time overlapping generations model for an endowment Arrow-Debreu economy with an age-structured population. For an economy with a balanced growth path, we prove that Arrow-Debreu equilibrium prices exist, and their dynamic properties are age-dependent. Our model allows for an explicit dependence of prices on critical age-specific endowment parameters. We show that, if endowments are distributed earlier than some critical age, then speculative bubbles for prices do exist.